Evaluation of elite table tennis players' technique effectiveness - Zhang, H.; Liu, W.; Hu, J.-J.; Liu, R.-Z. (Journal of Sports Sciences, 2013)
This study constructed a technique effectiveness evaluation formula for table tennis players based on the relationship between the scoring rate and usage rate of techniques and established the evaluation criteria through the examination of 224 matches of the world's top 35 players. It also built a competition performance formula with the score difference theory for the exploration of the correlation between player technique effectiveness and competition performance. The results showed the three indices - the technique effectiveness of the first and third strokes (TE1,3), the second and fourth strokes (TE2,4) and the after fourth strokes (TE>4) - could help better evaluate the technique effectiveness of elite players. The comparative analysis of Chinese elite table tennis players and players from other countries and regions revealed that Chinese players as a whole were "excellent" in all the examined techniques except in the male's "first and third strokes"; while players from other countries and regions were overall "general". The case analysis of two world top players further indicated that correlation analysis of technique effectiveness and competition performance could help identify the technique indices highly correlated with player competition performance.